2020
DOI: 10.1002/advs.201903368
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid Assisted Crystallization Strategy for High Efficiency and Long‐Term Stable Perovskite Solar Cell

Abstract: Improving the quality of perovskite poly‐crystalline film is essential for the performance of associated solar cells approaching their theoretical limit efficiency. Pinholes, unwanted defects, and nonperovskite phase can be easily generated during film formation, hampering device performance and stability. Here, a simple method is introduced to prepare perovskite film with excellent optoelectronic property by using acetic acid (Ac) as an antisolvent to control perovskite crystallization. Results from a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 54 publications
4
81
0
Order By: Relevance
“…The peak of the Pb-O bond can further be observed in Raman spectrum of the PbI 2 -MAAc film (Figure S17 ). These results confirm the strong interaction between undercoordinated Pb 2+ and O atom in Ac − , which are consistent with previous reports that the Lewis base site C=O group can provide an electron pair to the undercoordinated Pb 2+ in the perovskite, thereby effectively passivating the perovskite film [ 7 , 38 ]. Together with the hydrogen bonds, therefore, the diagram of grains and GBs of MAAc perovskites can be drawn in Figure 4(e) , in which the MAAc at GBs stabilized by intrinsic hydrogen bonding between MA + and Ac − can anchor perovskite octahedron through Pb-O (undercoordinated Pb 2+ of MAPbI 3 and C=O of MAAc), N-H⋯I (MA + of MAAc and I − of MAPbI 3 ), and N-H⋯O (MA + of MAPbI 3 and C-O of MAAc), which can effectively stabilize the structure of perovskite and inhibit defects [ 7 , 28 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The peak of the Pb-O bond can further be observed in Raman spectrum of the PbI 2 -MAAc film (Figure S17 ). These results confirm the strong interaction between undercoordinated Pb 2+ and O atom in Ac − , which are consistent with previous reports that the Lewis base site C=O group can provide an electron pair to the undercoordinated Pb 2+ in the perovskite, thereby effectively passivating the perovskite film [ 7 , 38 ]. Together with the hydrogen bonds, therefore, the diagram of grains and GBs of MAAc perovskites can be drawn in Figure 4(e) , in which the MAAc at GBs stabilized by intrinsic hydrogen bonding between MA + and Ac − can anchor perovskite octahedron through Pb-O (undercoordinated Pb 2+ of MAPbI 3 and C=O of MAAc), N-H⋯I (MA + of MAAc and I − of MAPbI 3 ), and N-H⋯O (MA + of MAPbI 3 and C-O of MAAc), which can effectively stabilize the structure of perovskite and inhibit defects [ 7 , 28 ].…”
Section: Resultssupporting
confidence: 92%
“…We dissolved PbI 2 into the MAAc solvent and investigated the characteristics of powders obtained from the PbI 2 -MAAc films. As shown in Figure S15 , the C=O vibration peak (1604.51 cm −1 ) in the PbI 2 -MAAc powder shifted to a low wavenumber as compared to C=O (1645.23 cm −1 ) in the pure MAAc, which is attributed to the coordination interaction between C=O of MAAc and undercoordinated Pb 2+ (I − vacancy) in the PbI 2 -MAAc films [ 38 ]. Moreover, we found that the position of Pb 2+ (4f 5/2 , 4f 7/2 ) in the PbI 2 -MAAc film has tendency towards lower binding energy relative to the PbI 2 -DMF film in the X-ray photoelectron spectroscopy (XPS) spectra (Figure S16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Y-Th2 chelated the Pb 2+ ions in perovskite, hydrophobically modified its surface, and immobilized the A-site cations (see Scheme 1). As evidenced in the blue-shifted X-ray photoelectron spectroscopy (XPS) spectra of Pb 4f at 138.7 eV and 142.8 eV and Fouriertransform infrared spectroscopy (FT-IR) spectra around 1700 cm −1 (Figure S2, Supporting Information), [33] the carbonyl functional groups of the rhodanine terminal moieties of Y-Th2 chelated with the uncoordinated Pb 2+ , passivating the defect sites of perovskite. The hydrophobicity of Y-Th2, conferred by a combination of its hydrocarbon side chains and its rigid conjugated backbone, is expected to mitigate the moisture infiltration of the perovskite.…”
Section: Resultsmentioning
confidence: 99%
“…The volatile FAAc that is obtained in the perovskite crystallization process can inhibit the degradation of perovskite. [151] A small amount of Ac reduces the roughness of the Figure 11. a) Schematic diagram and TEM image of the perovskite layer interface.…”
Section: Gb Engineeringmentioning
confidence: 99%
“…The volatile FAAc that is obtained in the perovskite crystallization process can inhibit the degradation of perovskite. [ 151 ] A small amount of Ac reduces the roughness of the perovskite film and the amount of residual PbI 2 , and it also generates a passivation effect with the electron‐rich carbonyl group (CO). Zhang et al showed that the 4‐aminobenzoic acid (ABA) as a nonvolatile additive could bridge the adjacent CsPbI 2 Br.…”
Section: Physical Passivationmentioning
confidence: 99%